Wolbachia-Based Population Control Strategy Targeting Culex quinquefasciatus Mosquitoes Proves Efficient under Semi-Field Conditions - Atyame, Célestine M. (PLoS One, 2015)
In mosquitoes, the maternally inherited bacterial Wolbachia induce a form of embryonic lethality called cytoplasmic incompatibility (CI). This property can be used to reduce the density of mosquito field populations through inundative releases of incompatible males in order to sterilize females (Incompatible Insect Technique, or IIT, strategy). We have previously constructed the LR[wPip(Is)] line representing a good candidate for controlling field populations of the Culex quinquefasciatus mosquito in the islands of the south-western Indian Ocean. The main purpose of the present study was to fill the gap between laboratory experiments and field implementation, i.e. assessing mating competitiveness of these incompatible males under semi-field conditions. In a first set of experiments, we analyzed crossing relationships between LR[wPip(Is)] males and La Réunion field females collected as larvae in 19 distinct localities throughout the island. This investigation revealed total embryonic mortality, confirming the strong sterilizing capacity of LR[wPip(Is)] males. Subsequently, mating competitiveness of LR[wPip(Is)] males was assessed under semi-field conditions in the presence of field males and females from La Réunion. Confrontations were carried out in April and December using different ratios of LR[wPip(Is)] to field males. The results indicated that the LR[wPip(Is)] males successfully compete with field males in mating with field females, displaying even higher competitiveness than field males in April. Our results support the implementation of small-scale field tests in order to assess the feasibility of IIT against Cx. quinquefasciatus in the islands of southwestern Indian Ocean where this mosquito species is a proven competent vector for human pathogens.